The genus Holaspis (Squamata: Lacertidae) in Angola: a tale of forgotten specimens and disappearing forests, with the description of a new species - Parrinha, Diogo; Marques, Mariana P.; Gonçalves, Francisco M. P.; Tiutenko, Arthur; Bauer, Aaron Matthew; Ceríaco, Luis M.P. (Salamandra, 2025)
The members of the Afrotropical lacertid genus Holaspis are strikingly specialized lizards, adapted for gliding in forest canopies, with serrated blue tails. Two species are currently recognized within the genus: Holaspis guentheri from West and Central Africa, and Holaspis laevis from East Africa. The currently known southern limits of H. guentheri are in the northern Angolan Guineo-Congolian habitats, which are remnants of forests connecting the country to West/Central Africa. The oldest record of the species in Angola, dating back to the 19th century, is based on a currently lost specimen collected by José d’Anchieta near Caconda, southwest Angola. Caconda is situated on the Angolan Central Plateau, which is part of the Great Escarpment of southern Africa. The loss of Anchieta’s specimen and its geographic context led most authors to disregard it, leaving its taxonomic identity dubious until now. The rediscovery of two additional specimens from Caconda, collected by William John Ansorge in the early 20th century and deposited in the Natural History Museum, London, allowed us to confirm the presence of the genus in the region, prompting targeted surveys and examination of additional material. Our surveys failed to locate any Holaspis near Caconda, with alarming rates of deforestation in the region raising the possibility that this population may already be extinct. The reexamination of the extant Caconda specimens and comparison with H. guentheri and H. laevis revealed consistent morphological differences that suggests that the Caconda population may represent a distinct taxonomic unit. Here we describe the Holaspis from Caconda as a new species, presumably endemic to the Angolan Central Plateau. These findings and their implications are discussed in the biogeographical context of the highlands of western Angola, a recognized hotspot of diversity and endemism for several taxonomic group
Keywords: Taxonomy; biogeography; natural history collections; deforestation; highlands; Lacertidae; Holaspis